2003
DOI: 10.1007/s00125-003-1041-8
|View full text |Cite
|
Sign up to set email alerts
|

HNF-6-independent differentiation of mouse embryonic stem cells into insulin-producing cells

Abstract: Aims/hypothesis. Embryonic stem cells, when grown as embryoid bodies, spontaneously generate insulinproducing cells which could be used in therapy of diabetes mellitus, provided that their selection and differentiation are optimized. To achieve such optimization, one needs to know whether the differentiation of cells in embryoid bodies mimicks that of pancreatic beta cells in embryos. To address this question we verified if the differentiation of the insulin-producing cells in embryoid bodies requires Hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, previous ES cell culture studies [25,[39][40][41][42][43][44] did not address nor specify the extent of endoderm and pancreatic differentiation in their cultures. Our results demonstrated that the S EB-derived population expressed both insulin I and II genes, as well as glucagon, pdx-1, and Sox17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous ES cell culture studies [25,[39][40][41][42][43][44] did not address nor specify the extent of endoderm and pancreatic differentiation in their cultures. Our results demonstrated that the S EB-derived population expressed both insulin I and II genes, as well as glucagon, pdx-1, and Sox17.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts have been directed at the generation of insulin-producing cells using the ES-EB culture system [25,[39][40][41][42][43][44] to provide islet cells for transplantation and cure of type I diabetes. However, previous ES cell culture studies [25,[39][40][41][42][43][44] did not address nor specify the extent of endoderm and pancreatic differentiation in their cultures.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reports have now demonstrated that ES cells can differentiate into cells with an insulin-expressing phenotype, either by genetic manipulation or by permitting spontaneous differentiation followed by culture under selective conditions (Soria et al 2000, Assady et al 2001, Lumelsky et al 2001, Hori et al 2002, Shiroi et al 2002, Blyszczuk et al 2003, Moritoh et al 2003, Miyazaki et al 2004, Segev et al 2004, Sipione et al 2004. In common with studies using tissue stem cells, the cellular identity of these insulin-expressing cells is uncertain and with the lack of specific, easily identifiable markers of a mature -cell, the possibility remains that these cells are not fully mature -cells but instead are a phenotypically similar population of cells, perhaps of neuroectodermal (Lumelsky et al 2001, Burns et al 2003 or extra-embryonic (Houard et al 2003) origin.…”
Section: Potential Sources Of Stem Cellsmentioning
confidence: 99%
“…There is some evidence that it may be possible to employ conscious design to arrive at the same end-point by a less circuitous route. Thus, it has been suggested that the pathways of -cell differentiation in vitro may differ significantly from those in vivo (Houard et al 2003) and mouse ES cells are reported to differentiate into endocrine cells without PDX-1 (pancreatic duodenal homeobox-1) expression (Moritoh et al 2003), although this is essential in vivo (Scharfmann 2000). It is also possible that current in vitro differentiation protocols do not generate -cells, but, instead, cells that have some phenotypic and functional similarity to authentic -cells.…”
Section: Ii) Do We Need To Make -Cells?mentioning
confidence: 99%
See 1 more Smart Citation